2020
DOI: 10.1249/mss.0000000000002476
|View full text |Cite
|
Sign up to set email alerts
|

Coingestion of Carbohydrate and Protein on Muscle Glycogen Synthesis after Exercise: A Meta-analysis

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…This finding was preserved when contextual factors were explored using metaregression analysis (Table 4). It is also consistent with results from previous meta-analyses indicating that coingestion of PRO with CHO during short-term recovery does not improve short-term muscle glycogen resynthesis [67] or subsequent exercise performance [68].…”
Section: Effect Of Cho+pro On Short-term Muscle Glycogen Resynthesissupporting
confidence: 91%
See 2 more Smart Citations
“…This finding was preserved when contextual factors were explored using metaregression analysis (Table 4). It is also consistent with results from previous meta-analyses indicating that coingestion of PRO with CHO during short-term recovery does not improve short-term muscle glycogen resynthesis [67] or subsequent exercise performance [68].…”
Section: Effect Of Cho+pro On Short-term Muscle Glycogen Resynthesissupporting
confidence: 91%
“…The authors hypothesised that the lower rate of muscle glycogen re-synthesis observed in the PRO trial may be due to AA triggering protein synthesis, resulting in glucose being oxidised to support the energy requirement for this process in place of glycogen storage [56]. Nonetheless, while the overall effect of our analysis suggests that co-ingesting PRO with CHO does not provide any benefit beyond that of CHO alone to muscle glycogen restoration (even when CHO intake is Table 2 The influence of contextual factors on the mean difference in rate of muscle glycogen re-synthesis (analysed via restricted maximum likelihood, simple meta-regression) for CHO vs. control treatments A recent meta-analysis [67] similar to the present study reported a significant main effect (favouring CHO+PRO over CHO) on muscle glycogen re-synthesis rate when the energy intake was not matched between treatments (non-isocaloric). This finding contrasts the results of the present study (Table 4).…”
Section: Effect Of Cho+pro On Short-term Muscle Glycogen Resynthesismentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, milk protein is expected to both promote and sustain muscle protein synthesis. A recent meta-analysis reported that glycogen synthesis rates are enhanced when carbohydrates and protein are co-ingested after exercise compared to carbohydrates only, when the added energy of protein is consumed in addition to, not in place of, carbohydrates, suggesting the importance of an increase in the energy intake [ 64 ]. It is well known that modulating postexercise nutrition is an effective approach to enhance the replenishment of muscle glycogen stores.…”
Section: Muscle Energy Metabolism and Nutrientsmentioning
confidence: 99%
“…We acknowledge that the collection of biopsy samples from adjacent, but non-identical sites, or sites from contra-lateral limbs in scenarios involving symmetrical exercise protocols, may contribute to the technical error of measurement involved with chemical determination of muscle glycogen stores. Nevertheless, it is the basis of a robust literature involving many hundreds of studies, which have determined resting muscle glycogen concentrations in different populations [ 36 ], glycogen utilisation during exercise [ 1 , 53 ], and glycogen synthesis in response to diet [ 19 , 54 , 55 ].…”
Section: Validity Of the Musclesound ® Technique: Location Of The Muscle Sitementioning
confidence: 99%